Multiwalled carbon nanotube forests grown on the surface of synthetic diamond crystals. Issue 13 (September 2017) - Bokhonov, B.B.; Ukhina, A.V.; Dudina, D.V.; Katsui, H.; Goto, T.; Kato, H.
Abstract: Forests of multiwalled carbon nanotubes (MWCNTs) were grown on the facets of synthetic diamond crystals by treating them in a rotary chemical vapor deposition reactor. Nickelocene was used as a source of both nickel catalyst and carbon for the formation of MWCNTs. The diamond crystals were not subjected to any surface treatment prior to the MWCNT growth. The MWCNTs were anchored in nickel particles adhered to the diamond facets and were partially filled with nickel. These morphological features of the diamond-MWCNT structures together with nanotube branching suggest the formation of MWCNTs by the combined growth mechanism.